2005
DOI: 10.1080/17461390500221610
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in handball: Examination of the risk factors

Abstract: This paper examines the influence of selected risk factors on injuries among male players of competition handball. Data relating to risk factors were collected using a self-report questionnaire. The factors that were examined were age, height, weight, body mass index, field position, past sport experience, level of competition, pre-season conditioning, number of practices per week, frequency of participation in games, use of prophylactic equipment, use of stretching exercises, and technical training. The quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Despite the multiple beneficial effects derived from handball practice, such as improvements in cardiovascular, metabolic, muscular and psychosocial health [4][5][6], this team sport presents a high injury risk [7], mainly due to its high-intensity specific demands (i.e., rapid changes of direction, jumps with abrupt landings and repetitive throws, as well as frequent physical contact among players [8,9]). Likewise, low physical fitness, incorrect technique, lack of flexibility, and also inadequate rehabilitation treatment of injuries have been reported as risk factors related to the occurrence of injuries [10,11]. Additionally, the high training volumes and intensities that youth players undertake to achieve sporting excellence seem to contribute to the increase of the injury incidence [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the multiple beneficial effects derived from handball practice, such as improvements in cardiovascular, metabolic, muscular and psychosocial health [4][5][6], this team sport presents a high injury risk [7], mainly due to its high-intensity specific demands (i.e., rapid changes of direction, jumps with abrupt landings and repetitive throws, as well as frequent physical contact among players [8,9]). Likewise, low physical fitness, incorrect technique, lack of flexibility, and also inadequate rehabilitation treatment of injuries have been reported as risk factors related to the occurrence of injuries [10,11]. Additionally, the high training volumes and intensities that youth players undertake to achieve sporting excellence seem to contribute to the increase of the injury incidence [10].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, low physical fitness, incorrect technique, lack of flexibility, and also inadequate rehabilitation treatment of injuries have been reported as risk factors related to the occurrence of injuries [10,11]. Additionally, the high training volumes and intensities that youth players undertake to achieve sporting excellence seem to contribute to the increase of the injury incidence [10]. In this regard, injuries are associated with negative consequences, such as a reduction of team success [12], an increment of costs related to treatments [13], and the risk of suffering new injuries [14].…”
Section: Introductionmentioning
confidence: 99%
“…Handball is categorized as a contact sport where physical contact and aggressiveness is present in the game (Prieto & Gómez, 2012). These characteristics make handball a sport with a great incidence of injuries (Lindblad, Jensen, Terkelsen, & Helleland, 1993;Tsigilis & Hatzimanouil, 2005), which increases with performance level (Langevoort, Myklebust, Dvorak, & Junge, 2007). The following most common research topics were physical capacities and conditions, physiological variables measurement, performance and success variables, and sport technique.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore field position is another factor over which there is conflicting evidence and refers to gender. Tsigilis and Hatzimanouil (2005) and Seil et al (1998), did not find any significant differences among the field positions in relation to the risk injury of male VOLUME 10 | ISSUE 4 | 2015 | 906 team handball players. On the other hand, Wedderkopp et al (1999) reported a higher injury incidence in female backcourt players, whereas Biener & Perka (1980) reported that middle-field females sustained more injuries.…”
Section: Introductionmentioning
confidence: 97%